2014
DOI: 10.1007/s13762-014-0562-7
|View full text |Cite
|
Sign up to set email alerts
|

Emission factors of air pollutants from vehicles measured inside road tunnels in São Paulo: case study comparison

Abstract: Burning of fuels from the transport sector is one of the main sources of air pollutants emission in urban areas. In order to implement public policies concerning air quality and public health, there is a need to develop emission inventories. Measurements inside traffic tunnels can provide an evaluation of emission factors of vehicles in-use in real conditions. In this paper, we show measurements of air pollutants for a mixed vehicle fleet, heavyand light-duty vehicles (HDVs and LDVs), in two tunnels in the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 41 publications
1
57
1
9
Order By: Relevance
“…Tunnel measurements were taken in order to characterize the true nature of the vehicle fleet in the MASP. In one tunnel study, Pérez-Martínez et al [12] showed that the emission factors of regulated pollutants were higher than those presented in official reports (CETESB, 2014). The authors compared their data with those of analyses performed under the same conditions in 2004 [11,13].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Tunnel measurements were taken in order to characterize the true nature of the vehicle fleet in the MASP. In one tunnel study, Pérez-Martínez et al [12] showed that the emission factors of regulated pollutants were higher than those presented in official reports (CETESB, 2014). The authors compared their data with those of analyses performed under the same conditions in 2004 [11,13].…”
Section: Introductionmentioning
confidence: 86%
“…The authors compared their data with those of analyses performed under the same conditions in 2004 [11,13]. The CO and nitrogen oxide (NO x ) emission factors reported by Pérez-Martínez et al [12] for light-duty vehicles in 2011 were both significantly (2.2 times) lower than those reported by Martins et al [13] for light-duty vehicles in 2004, whereas they were five times and 2.5 times lower for CO and NO x , respectively, from heavy-duty vehicles. Analyzing the number and mass size distribution of particles, Pérez-Martínez et al [12] calculated the PM 2.5 emission factor to be 20 mg/km for light-duty vehicles and 277 mg/km for heavy-duty vehicles, showing the great contribution of diesel to the emission of fine particles.…”
Section: Introductionmentioning
confidence: 99%
“…The modeling approach taken in different cities in the southeastern region of Brazil has been evolving, and most of the efforts have been focused on the construction of a comprehensive emissions inventory. In the MASP, the emissions inventory is based on vehicle emission factors (dynamometer measurements) and tunnel measurements performed in the city of São Paulo in 2001and 2004Sánchez-Ccoyllo et al, 2009), as well as on experiments conducted in 2011 Pérez-martínez et al, 2014).…”
Section: Wwwfrontiersinorgmentioning
confidence: 99%
“…The modeling capability has been increased by experimental studies aimed at improving the emissions inventory and describing the atmospheric processes. Such experiments consist of measurements of ozone precursors ; fine and ultrafine particles (Almeida et al, 2014); and emission factors Pérez-martínez et al, 2014). Combining all the efforts that have been applied to the representation of pollutants with air quality models in the MASP, an operation was implemented in order to forecast the concentrations of ozone, carbon monoxide, and particles.…”
Section: Wwwfrontiersinorgmentioning
confidence: 99%
See 1 more Smart Citation